7.6k views
2 votes
(7x - 6 1/2 ) - (-5x - 3 3/5)

User Aankhen
by
5.7k points

1 Answer

2 votes

Answer:


\huge\boxed{12x-2(9)/(10)=12x-2.9}

Explanation:


\left(7x-6(1)/(2)\right)-\left(-5x-3(3)/(5)\right)\\\\=7x-6(1)/(2)+5x+3(3)/(5)\qquad\text{combine like terms}\\\\=(7x+5x)+\left(-6(1)/(2)+3(3)/(5)\right)\qquad\text{find LCD}=10\\\\=12x+\left(-6(1\cdot5)/(2\cdot5)+3(3\cdot2)/(5\cdot2)\right)\\\\=12x+\left(-6(5)/(10)+3(6)/(10)\right)\\\\=12x-\left(6(5)/(10)-3(6)/(10)\right)\\\\=12x-\left(5(10+5)/(10)-3(6)/(10)\right)\\\\=12x-2(15-6)/(10)\\\\=12x-2(9)/(10)

User Manuel Spezzani
by
6.1k points